Association of Pharmacologic Treatment of Urgency Urinary Incontinence With Sleep Quality and Daytime Sleepiness. Issue 5 (May 2018) - Warsi, Qurratul A.; Huang, Alison J.; Hess, Rachel; Arya, Lily A.; Richter, Holly E.; Bradley, Catherine S.; Rogers, Rebecca G.; Myers, Deborah L.; Johnson, Karen C.; Winkelman, William D.; Gregory, W. Thomas; Kraus, Stephen R.; et al.
Abstract : (Abstracted from Obstet Gynecol 2018;131:204–211) Both incontinence and sleep disturbance are common and bothersome conditions in middle-aged and older women. Any treatment that improves both conditions may provide clinical value.